Mechanical properties of microsphere based composite materials - Rajkumar, Ananth (2012)
In this experimental study two different types of composite materials were prepared and their mechanical behavior was investigated. The first group consists of porous material made from sintering a mixture of micron size glass and metal spheres. Though the porous compacts made from glass microspheres have been already investigated, the main aim of the present work is to study the effect of varying the proportion of the metal spheres on the mechanical strength of the final sintered porous material. The results presented herein show that mixing metal microspheres always results in diminishing of the fracture strength of the final material and the decrease is first proportional to the volume ratio but after a certain percentage the material becomes very week; a provisional explanation is suggested. The fracture path and surface in disc type specimen broken under a flexural stress were also studied by optical microscopy. The second composite material studied consists of hollow metal spheres embedded in a polymer matrix; the general aim is to prepare lightweight armour for energy absorption under impact. Composites were made by mixing the millimeter size hollow aluminum spheres in a two-part epoxy and subsequent thermal curing of the mixture. The tests on the cured samples showed that they generally had many voids and the strength was low. An improved procedure was devised that led to considerable reduction of voids and consequently an improvement in the strength.